Modified Kessler technique for extensor tendon reconstruction: a case report - Rodriguez, Jose M. H.; Valerio, Victor M. O.; Villa, Jessica C. R.; Sanchez, Irvin H.; Mora, Melissa R.; Martinez, Felix A. D.; Garcia, Edgar A. F.; Morales, Gadiel E. P. (International Surgery Journal, 2026)
Tendon injuries in the upper extremities are among the most prevalent types of traumatic injuries that are seen in emergency rooms. Due to the fact that the mechanism of the extensor is distinct from the mechanism used by the flexor system, it can be difficult to execute surgery to correct the issue. Discovering the optimal equilibrium between tendon mobility, sliding, and joint stability is the single most significant factor in determining one's level of competitiveness.